The contribution of underwater kicking efficiency in determining "turning performance" in front crawl swimming - Zamparo, P.; Vicentini, M.; Scattolini, A.; Rigamonti, M.; Bonifazi, M. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to analyze the effects: 1) of maximal velocity (vout max) and acceleration (aout max) attained during the turn; 2) of deceleration (-aglide) and glide efficiency (GE) in the gliding phase after the turn; and 3) of the efficiency (hF) of the dolphin kick in determining the velocity and acceleration in the first 5 and the following 10 m after a turn (v5, v5-15, a5 and a5-15) in a 100 m simulated front crawl race. METHODS: The experiments were conducted on 13 swimmers (7M/5F) and all the above mentioned parameters were derived from underwater kinematical analysis. RESULTS: The 100 m times were smaller the larger v5, v5-15, a5 and a5-15. In turn, v5, v5-15, a5 and a5-15 were significantly related to vout max and aout max as well as to nyF and GE (R>0.57, CONCLUSION: Data reported in this study indicate that in the first 5-15 m after the turn, velocity is essentially sustained by the force generated by the swimmer on the pool wall but also indicate the importance of an efficient dolphin kick (and of a streamlined glide) in determining the values of velocity and acceleration in this phase of the race.